Indonesia ANALISIS PENGGUNAAN MEDIA YOUTUBE TERHADAP IKLAN SHOPEE PADA MASYARAKAT GEN Z DESA BELIK, KECAMATAN PRACIMANTORO, KABUPATEN WONOGIRI TAHUN 2023 - Alfarizqi, Mochamad Aldifa (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2024)
This research aims to analyze the use of YouTube media among Gen Z in BelikVillage, Pracimantoro District, Wonogiri Regency in 2022. The research design used inwriting this thesis is a type of qualitative research using Harrold Lasswell's communicationtheory. The research subjects were Gen Z in Belik Village. There are two types of data used,namely primary data and secondary data using in-depth interview data collection techniquesdirectly or online and related documents. The research results show that the use of YouTubemedia has an impact on determining the Gen Z group in Belik Village in making decisions, inthis case the decision to shop through Shopee. The type of Shopee advertisement that is oftenbroadcast via YouTube is promos or discounts with the same date and month format. Mostchoose this promo to buy make up and electronic equipment.Keyword: Gen Z, Shopee Ads, YouTube Media